1991
DOI: 10.1159/000177651
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Responses to Exercise in Hepatic Ketogenesis and Lipid Secretion in the Rat

Abstract: The effects of 4 weeks of voluntary exercise (rotating wheel) on serum and liver lipid levels were studied in 6-week-old male Wistar rats. The hypotriglyceridemic effect of exercise was not influenced by the dietary fat levels (4.5 and 14.5%), whereas the hypocholesterolemic effect was higher in a low-fat diet than in a high-fat diet. Although the serum cholesterol-lowering effect of exercise was marginal, the beneficial effect on hepatic lipids was observed only in rats fed a high-cholesterol diet. The hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
2
21
0
1
Order By: Relevance
“…One explanation may be that exercise decreased hepatic TG secretion, 31 partly by altering hepatic partitioning of fatty acids between esterification and oxidation. 32 In line with this thinking, the reduction in the postprandial 3-hydroxybutyrate response by the high-CHO intervention was somewhat attenuated by exercise (Table 4, Figure 3). Another explanation may be that exercise opposed the suppressive effects of a diet high in carbohydrates on LPL activity.…”
Section: Koutsari Et Alsupporting
confidence: 65%
“…One explanation may be that exercise decreased hepatic TG secretion, 31 partly by altering hepatic partitioning of fatty acids between esterification and oxidation. 32 In line with this thinking, the reduction in the postprandial 3-hydroxybutyrate response by the high-CHO intervention was somewhat attenuated by exercise (Table 4, Figure 3). Another explanation may be that exercise opposed the suppressive effects of a diet high in carbohydrates on LPL activity.…”
Section: Koutsari Et Alsupporting
confidence: 65%
“…The present studies showed similar results (Table 3). These observations therefore suggest that the hypocholesterolemic effect of dietary taurine results partly from a decreased rate of hepatic secretion of cholesteryl ester, since the influx of cholesterol entering the blood stream from the liver in the form of lipoprotein-cholesterol is a critical determinant of serum cholesterol concentration (22).…”
Section: Discussionmentioning
confidence: 90%
“…Along with an increase in LPL activity, very low density lipoprotein (VLDL) secretion from the liver may be reduced by an acute exercise bout (41). In humans, reductions in postprandial plasma concentration of VLDL-TG has been shown to be reduced following exercise (39,59) and in mice, reduced postprandial secretion of VLDL from the liver has been observed after exercise (36,65). Resistance training and high-intensity interval training have also been shown to be effective for reducing PPL; however, energy expenditure does not seem to predict the attenuation as well as with aerobic exercise (5,22,93).…”
Section: Exercise and Lipid Metabolismmentioning
confidence: 99%